Faktor-Faktor Penentu Penghindaran Pajak pada Perusahaan Multinasional Sektor Consumer Non-Cylicals - Winda Silviana; Marita Marita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tax avoidance practices remain an important issue in Indonesia's taxation system, estimated to cause the state to lose up to US4.86 billion in revenue. This study aims to examine the extent to which Capital Intensity, Sales Growth, and Accounting Conservatism play a role in influencing the level of Tax Avoidance. The research approach uses a quantitative method based on a literature study, with multiple linear regression analysis as the main technique. The theoretical basis refers to Positive Accounting Theory and Agency Theory to explain the motivation and behavior of companies in determining tax policy. Capital Intensity and Accounting Conservatism do not influence Tax Avoidance practices. Conversely, Sales Growth is proven to have a positive and significant effect, indicating that an increase in sales growth can open up more space for companies to manage profits that have implications for tax liabilities. Overall, these findings confirm that the dynamics of sales growth play a more decisive role than capital intensity or accounting conservatism in influencing tax avoidance practices.